Media Buku Pop Up Pembelajaran Bahasa Jawa Anak Sekolah Dasar - Kusumoningrum, Ipung Dyah; Handriyotopo, Handriyotopo (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Writing a Javanese script to make it easy to understand requires interactive learning media by designing interactive pop-up books for elementary school students in Surakarta. The design of a pop-up book in Javanese with a qualitative methodology to collect data through interviews with teachers, the education office, and references to the Javanese curriculum. Pop up book design methods, namely; 1 (first) determine the theme and content of the page, scriptwriting style, visual style, visualization techniques, making interactive pop-up book models. The 2nd (two) make the title design, color selection, design pages with attractive illustrations, as well as selecting materials that are suitable for use. The 3rd (three) determines the illustrations and pop-up techniques used on each page. Promotional media for the introduction of Javanese script pop up books to the public, through social media, namely; Youtube and Instagram, supported by media posters, x banners, and gifts in the form of drinking bottles and character magnets. The design of interactive Javanese pop-up books is visually attractive and has a positive impact on students to focus on learning better, as a teaching medium for teachers in the classroom.